PENGEMBANGAN LKPD PJOK MATERI PENANGANAN CEDERA RINGAN SESUAI PRINSIP PERTOLONGAN PERTAMA PADA KELAS IV A DI UPTD SDN KAMAL 2 - Fefi Utami; Jannah, Ana Naimatul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to develop a Student Worksheet (LKPD) for Physical Education, Sports, and Health (PJOK) based on the Student Teams Achievement Division (STAD) cooperative learning model on the topic of minor injury management according to first aid principles for Grade IV-A students at Kamal 2 elementary school. The developed product was expected to be valid, effective, and attractive. This study was motivated by the limited use of teaching materials in PJOK learning in the classroom, and the learning process was still teacher-centered. This research employed the 4D development model, consisting of four stages: Define, Design, Development, and Disseminate. The research subjects were 27 Grade IV-A students of Kamal 2 elementary school. The results indicated that the STAD-based cooperative PJOK LKPD developed in this study was valid, effective, and attractive. The validity of the product was assessed by a teaching material expert, an instructional design expert, and a subject matter expert, yielding scores of 88.3% (very valid), 90% (very valid), and 95% (very valid), respectively. The effectiveness of the LKPD was evaluated through observations of teacher and student activities as well as students’ cognitive learning outcomes. The percentage of teacher activity observation reached 96.67%, categorized as “very effective,” while student activity observation achieved 90.5%, also categorized as “very effective.” The cognitive learning outcomes showed that 100% of the students achieved classical learning mastery, categorized as “mastery achieved.” The attractiveness of the LKPD, based on the teacher response questionnaire, obtained a score of 100% and was categorized as “very attractive,” while the student response questionnaire yielded a score of 97%, also categorized as “very attractive.” Keywords: LKPD, PJOK, STAD